PERILAKU KONSUMTIF GENERASI Z: ANALISIS HEDONISME DI KALANGAN PENERIMA KIP - Willa Putri Malinda Buchori; Septiningdyah Arianisari; Lu'lu'ul Jannah; Syahida Norviana (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
This article discusses the consumptive behavior of Generation Z recipients of the Indonesia Smart Card (KIP) with a focus on hedonic analysis and challenges in financial management. This study uses a qualitative approach with in-depth interviews with Generation Z students who are KIP recipients at Yogyakarta State University. Findings indicate variations in financial use and planning, but challenges such as delayed fund disbursement and unexpected expenses hinder their ability to save. KIP recipients struggle to balance hedonism and financial responsibility, with some sacrificing essential needs for hobbies or self-reward, leading to impulsive purchases that often result in regret. Additionally, the social impact of consumerist behavior is evident in the pressure to follow trends, which can lead to bullying and feelings of envy, with many students influenced by the FOMO phenomenon and social media encouraging impulsive spending. This article recommends the need for financial literacy education and social support to help students manage their funds wisely.